Phylogeographical Pattern and Population Evolution History of Indigenous Elymus sibiricus L. on Qinghai-Tibetan Plateau - Han, Mengli; Zhang, Jingxue; Li, Daxu; Sun, Shengnan; Zhang, Changbing; Zhang, Chuanjie; Yan, Lijun; Guan, Yongzhuo; Chen, Lili; Guo, Yuxia; You, Minghong; Gou, Wenlong; et al. (Frontiers in Plant Science, 2022)
Elymus sibiricus L. is a perennial allotetraploid belonging to Triticeae of Poaceae, Elymus L., as the type species of genus Elymus L. The existing geographical distribution pattern and genetic spatial structure of E. sibiricus on Qinghai–Tibetan Plateau (QTP) are not yet clear. In this study, population genetic structure and demography history of 216 individuals from 44 E. sibiricus populations on QTP were studied used specific-locus amplified fragment sequencing (SLAF-seq). The result of genetic diversity showed that there was no single genetic diversity center was observed across all E. sibiricus populations. The results of genetic variation showed that 44 populations were clearly divided into the following three groups: Qinghai Plateau (Group I), South Tibet (Group II), and Hengduan Mountains (Group III). From the three analyses of AMOVA, Mantel test and Treemix, strong genetic differentiation across all populations and low genetic differentiation among populations within three groups. Molecular dating indicated that E. sibiricus diverged at 16.08 Ma (during the early Miocene) can be linked to the Himalayan Motion stage of QTP uplift. It is speculated that the reasons affecting the current phylogeographical pattern are as follows: (1) The environmental changes due to the uplift of the QTP; (2) The geographic distance between the populations (Groups I and III are close in geographic distance, and gene flow are frequent); (3) Geographical barriers (the Tanggula and Bayangela Mountains between Groups I and II). This study provides new evidence and historical perspective to the future exploration of the evolution and geographic distribution pattern of Elymus L.